Pemberdayaan Masyarakat dalam Pengembangan Industri Rumah Tangga Sambal Matah Baby Cumi di Kelurahan Air Dingin - Hermita, Neni; Putra, Zetra Hainul; Alpusari, Mahmud; Alim, Jesi Alexander; Dahnilsyah, Dahnilsyah; Joleha, Joleha; M. Yogi Riyantama Isjoni; Nurrafiah, Efrida Yuslia; Kholiyanti, Nur; Yurisa, Yurisa; Aljita, Deni; Syahputra, Anugrah Kharisma; Santika, Yuyun; Bantala, Adam Yulyan; Harahap, Alma Rifaldy; Ramadhani, Khairunnisa; Barus, Albianus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The Riau University student community service team empowers the community by developing products that can be used as souvenirs of cold water. Cold water itself is a village located in Pekanbaru. The purpose of this community empowerment is to develop the potential of the cold water community, increase community income, and is expected to open up job opportunities for the surrounding community. In addition, the community service team also informs business actors to provide appropriate packaging, starting from packaging and product design. This is so that the product can compete with existing commodities. With an attractive packaging supported by a contemporary design, it will be the main attraction but it can also add to the selling value of a product. Of course, this is also accompanied by marketing through social networks such as Facebook, Instagram, and Whatsapp.